Gymnaster koraiensis and its major components, 3,5-di-O-caffeoylquinic acid and gymnasterkoreayne B, reduce oxidative damage induced by tert-butyl hydroperoxide or acetaminophen in HepG2 cells - Jho, Eun Hye (Korean Society for Biochemistry and Molecular Biology, 2013)
We investigated the protective effects of Gymnaster koraiensis against oxidative stress-induced hepatic cell damage. We used two different cytotoxicity models, i.e., the administration of tert-butyl hydroperoxide (t-BHP) and acetaminophen, in HepG2 cells to evaluate the protective effects of G. koraiensis. The ethyl acetate (EA) fraction of G. koraiensis and its major compound, 3,5-di-O-caffeoylquinic acid (DCQA), exerted protective effects in the t-BHP-induced liver cytotoxicity model. The EA fraction and DCQA ameliorated t-BHP-induced reductions in GSH levels and exhibited free radical scavenging activity. The EA fraction and DCQA also significantly reduced t-BHP-induced DNA damage in HepG2 cells. Furthermore, the hexane fraction of G. koraiensis and its major compound, gymnasterkoreayne B (GKB), exerted strong hepatoprotection in the acetaminopheninduced cytotoxicity model. CYP 3A4 enzyme activity was strongly inhibited by the extract, hexane fraction, and GKB. The hexane fraction and GKB ameliorated acetaminophen-induced reductions in GSH levels and protected against cell death. [BMB Reports 2013; 46(10): 513-518]